Caste-Based Discrimination, Microfinance Credit Scores, and Microfinance Loan Approvals Among Females in India. Issue 2 (February 2022) - Patel, Pankaj C.; Lenka, Sambit; Parida, Vinit
We draw on the phenomenon of caste-based discrimination in India and signaling theory to assess whether microfinance credit scores improve the odds of female micropreneurs from a lower caste receiving loans and whether visible business characteristics further improve the odds of receiving microfinance loans. In a sample of 3, 144 female microfinance loan applicants at a female-focused microloan enterprise in India, females from a lower caste, relative to those from a higher caste, have lower odds of receiving loans when their credit scores are below the mean. However, when females from a lower caste have credit scores higher than the mean, the odds of receiving a loan increase. The practical effect of size is small but meaningful. Loan applicants from a lower caste with a visible signal of business ability do not improve their chances of receiving a loan relative to those from a higher caste.